An analysis of hybrid hidden Markov models for cetacean detection - Edwards, David James Erich (Stellenbosch : Stellenbosch University, 2025)
Edwardsr, D. J. E. 2025. An analysis of hybrid hidden Markov models for cetacean detection. Unpublished masters thesis. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/6d13104b-e940-4f3d-aa3d-7ec19d1ee487